Penerapan Nilai-Nilai Pancasila dalam Kehidupan Kampus - Nuramalina, Nuramalina; Nur Rimadhani, Silvia; Arjuna Isabel, Rosalinda Jaya; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Pancasila as the basis of the state has an important role in shaping the character of the nation, including in higher education. Campus is a strategic place to instil and apply Pancasila values, such as mutual respect, justice, and responsibility. This study aims to analyse the extent to which Pancasila values are applied in student life. The research method used is a survey using google form by involving active students of Surabaya State University as respondents. The results showed that most students apply mutual respect in campus life, both through daily interactions and cooperation in groups. Fairness is also reflected in decision-making or task distribution, which is often done collectively and based on deliberation. However, there are still some students who are not consistent in applying these values, especially in situations that require quick decision-making or conflict. These findings indicate the need to strengthen Pancasila-based character education through various academic and non-academic programmes that support the implementation of these values in a sustainable manner.